Peran Dalam Dampak Tingkat Pelayanan Pajak Di Tingkat Pembayaran Pajak Tanah Dan Banguan Guna Peningkatan Dalam Pendidikan Pajak dan Sanksi Pajak Bumi Dan Bangunan - Wardani, Nindi Anggi; Wibawa, Eka Satria; Henny , Henny (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2022)
Tax income indicates that tax revenue is very important in the role of reporting Land and Building Tax Payments which has been equated with the level of compliance with Land and Building Tax Payments in reporting taxes to the State. In 2019 to 2021 there are many delays in reporting Land and Building Taxpayers resulting in little State tax revenue. Based on research data, the list of land and building tax payments is 8,756,505. Until the end of 2020, there were 9,875,810 registered based on this data. It is known that the annual Land and Building Tax Payer Reports registered 1375% of the 2019 Land and Building Tax Payment report. In 2021, the entire list of Land and Building Tax Payer users is from 11, 5 Million of Population. Explaining that the variable quality of tax services (X1) has a minimum answer of 15 respondents while the maximum is 25, with an average of 21.1656 and a standard deviation of 1.66305. The awareness variable of Land and Building Tax Payers (X2) has a minimum respondent answer of 15 while a maximum of 25, with an average of 21.3841 and a standard deviation of 1.75446